STRENGTHENING STUDENT COMPETENCE THROUGH IN DEEP LEARNING TOWARDS THE ACHIEVEMENT OF PANCAWALUYA BASED CHARACTER - Fahriansyah, Faisal; Santyasa, I Wayan; Agustini, Ketut; Suartama, I Kadek; Walidain, Birrul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The development of student competence and character has become a central concern in contemporary education, particularly in responding to global challenges that require higher-order thinking skills and strong moral foundations. This study aims to examine how the deep learning approach contributes to strengthening student competence toward the achievement of Pancawaluya-based character values. The research employed a Systematic Literature Review (SLR) method guided by PRISMA procedures. Relevant literature was collected from academic databases such as Google Scholar, DOAJ, and Scopus using keywords related to deep learning, student competence, character education, and Pancawaluya. After a rigorous screening and eligibility process, 20 articles published within the last ten years were selected and synthesized for analysis. The results indicate that the deep learning approach significantly enhances higher-order cognitive skills, metacognitive awareness, critical thinking, collaboration, and reflective abilities. Furthermore, when integrated with Pancawaluya values cageur, bageur, bener, pinter, and singer the deep learning approach facilitates holistic character formation through authentic, contextual, and participatory learning experiences. The discussion highlights that meaningful engagement, reflective activities, and project-based collaboration are effective mechanisms for internalizing local cultural values within academic processes.The novelty of this study lies in conceptualizing the integration of the deep learning approach with the local wisdom framework of Pancawaluya as a comprehensive model for competence and character development. The findings imply that educators and policymakers should systematically embed culturally grounded character values into deep learning design to promote sustainable, holistic, and culturally responsive education.